Improvement in rice seed storage longevity from high-temperature drying is a consistent positive function of harvest moisture content above a critical value - Whitehouse, K.J.; Hay, F.R.; Ellis, R.H. (Cambridge University Press, 2018)
Drying reduces seed moisture content, which improves subsequent seed survival periods. Diverse maximum temperatures have been recommended to limit or avoid damage to seeds, but some high-temperature drying regimes may improve subsequent seed quality. Seeds from 20 different accessions of five rice (Oryza sativaL.) variety groups (aromatic, Aus, Indica, temperate Japonica, tropical Japonica) were harvested over several seasons at different stages of maturation and either dried throughout at 15°C/15% relative humidity (RH) or for different initial periods (continuous or intermittent) in different drying regimes at 45°C before final equilibrium drying at 15°C/15% RH. Subsequent seed longevity in hermetic storage at 45°C with 10.9% moisture content was determined. In no case did initial drying at 45°C provide poorer longevity than drying at 15°C/15% RH throughout. There was a split-line relation, which did not differ amongst investigations, between longevity after initial drying at 45°C relative to that at 15°C/15% RH throughout and harvest moisture content, with a break point at 16.5% (a seed moisture status of about –14 MPa). Below 16.5%, relative longevity did not differ with harvest moisture content with little or no advantage to longevity from drying at 45°C. Above 16.5%, relative longevity showed a positive relation with harvest moisture content, with substantial benefit from drying at 45°C to subsequent longevity of seeds harvested whilst still moist. Hence, there are temporal (immediatelyex plantacf. subsequent air-dried storage) and water status discontinuities (above cf. below 16.5%) in the effect of temperature on subsequent air-dried seed longevity.